1996
DOI: 10.1021/ja954202k
|View full text |Cite
|
Sign up to set email alerts
|

Electron Photodetachment Spectroscopy of Solvated Anions:  RO·HF-or ROH·F-?

Abstract: Electron photodetachment spectra of three alkoxide ions, 2,2-dimethyl-3-pentoxide, 3,3-dimethyl-2-butoxide, trifluoroethoxide, and two complex ions, 3,3-dimethyl-2-butanol/fluoride, 2,2-dimethyl-3-pentanol/fluoride, have been measured using an ion cyclotron spectrometer to generate, trap, and detect the ions. The electron affinities of trifluoroethoxide, 2,2-dimethyl-3-pentoxide, and 3,3-dimethyl-2-butoxide were measured as 58.9 ( 0.1, 47.8 ( 0.3, and 45.7 ( 0.1 kcal mol -1 , respectively. Using known proton a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 62 publications
0
27
0
Order By: Relevance
“…As shown in Scheme 1, it is believed that a percentage of the alcohol molecules first undergo dissociative electron capture to produce F Ϫ , a process that is common for fluorinated materials [27]. An alcohol molecule is then observed to complex with the F Ϫ in a fashion similar to that shown by Brauman et al [28] The telomer alcohols, in comparison to the 7:1 alcohol, do not appear to undergo any appreciable dimerization. This is likely due to decreased hydrogen bonding between molecules which results from the decreased acidity of the -OH group when the CF 2 moiety is in the ␤ position rather than the ␣ position relative to it.…”
Section: Negative Chemical Ionization Pathways For Fluorinated Alcoholsmentioning
confidence: 75%
“…As shown in Scheme 1, it is believed that a percentage of the alcohol molecules first undergo dissociative electron capture to produce F Ϫ , a process that is common for fluorinated materials [27]. An alcohol molecule is then observed to complex with the F Ϫ in a fashion similar to that shown by Brauman et al [28] The telomer alcohols, in comparison to the 7:1 alcohol, do not appear to undergo any appreciable dimerization. This is likely due to decreased hydrogen bonding between molecules which results from the decreased acidity of the -OH group when the CF 2 moiety is in the ␤ position rather than the ␣ position relative to it.…”
Section: Negative Chemical Ionization Pathways For Fluorinated Alcoholsmentioning
confidence: 75%
“…However, rate enhancement relative to the solution reaction requires that the strengthening of the H bond to enzymatic catalytic groups be greater than that to water. The steeper dependences of H bond strength on ⌬pK a generally observed in organic solvents and the gas phase than in water suggested that this is possible (10,11,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)36). However, we were aware of no direct comparison of these dependencies in nonaqueous and aqueous media.…”
Section: Discussionmentioning
confidence: 89%
“…DMSO may therefore provide a crude mimic for the environment in an enzymatic interior, despite its high bulk dielectric constant. In general, larger Brønsted slopes for H bonds are observed in nonaqueous solutions than in water (10,11,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)36).…”
Section: Origins Of the Larger Brønsted Slopes Of H Bonding Inmentioning
confidence: 99%
“…In a comparative order of magnitude are also the bond strengths in aliphatic ethers (340 kJ mol −1 ) [ 89 ]. The O−H bond in aliphatic alcohols is still considerably stronger (435 kJ mol −1 ) [ 91 , 92 ]. With these data in mind, comparison with the results in Table 2 revealed that the ratio of the epoxy ketones 13a/b vs. spiro ketone 14 directly reflected the energy of the O−X bond.…”
Section: Resultsmentioning
confidence: 99%